Business Regulatory Framework - Dash, Purnakam; Dash, Purnakam (Pearson India, 2011)
The legal environment constitutes an important aspect of business and therefore forms an indispensable part of the commerce curriculum. This engaging, visually appealing text will help students develop a thorough understanding of the legal environment in business and enhance their ability to critically engage with issues pertaining to business ethics. Covering around 50 cases and 300 questions and including all judiciary and statutory developments that have transpired so far, the book is ideal for students studying in various universities and autonomous colleges of Odisha.